Effect of trisodium citrate on the gelation properties of casein/gellan gum double gels formed at different temperature - Weibo Zhang; Liang Zhao; Jing Wang; Yao Hu; Yi Wang; Pengjie Wang; Jiaqi Su; Hao Zhang; Ran Wang; Fazheng Ren; Chong Chen (Carbohydrate Polymer Technologies and Applications)
Gellan gum (GG) is widely used in the dairy products to enhance stability of casein (CN)-based gel by forming double gels. Ca2+ is reported to facilitate GG gel formation, however, the effect of Ca2+ on the gelation properties of CN/GG double gels remains unknown. In the study, the behavior of Ca2+was regulated by trisodium citrate (TC). TC decreased the water-holding capacity (WHC) and storage modulus (G') of CN/GG gels formed at 37℃. Whereas CN/GG gels with 30 mmol/L TC formed at 42℃ (42–30) exhibited the highest values of WHC and G' among that with 0–15 mmol/L TC. These results suggested TC had different effect on the gelation properties of the CN/GG gels formed at 37℃ and 42℃ with different gelation sequence. Mechanically, TC did not change the gelation sequence of CN/GG gels, which increased the free water content and caused larger void in CN/GG gels formed at 37℃, resulting in decreased WHC and G'. While TC-induced larger void slightly destroyed the continuity of CN gel in 42–30 sample and the addition of TC enhanced the individual CN gel, leading to higher WHC and G′. Overall, these findings demonstrated that TC's effect on CN/GG gels at 37℃ and 42℃ was contrary, which provided substantial basis for revealing the gelation mechanism of CN-based double gels.